The Pseudomonas aeruginosa Type III secretion system plays a dual role in the regulation of caspase-1 mediated IL-1β maturation - Galle, M (Blackwell Publishing Ltd, 2008)
Pseudomonas aeruginosa is an opportunistic bacterial pathogen that forms a serious problem for immunocompromised patients and also the leading cause of mortality in cystic fibrosis. The overall importance of a functional Type III secretion system (T3SS) in P. aeru inosa virulence has been well established, but the underlying mechanisms are still unclear. Using in vitro infected macrophages as w as a murine model of acute lung infection, we show that the Caspase-1 mediated maturation and secretion of IL-1β needs a translocation competent T3SS and Flagellin, but not the Type III effector proteins ExoS, ExoT and ExoY. However, ExoS was found to negative regulate the P. aeruginosa induced IL-1β maturation by a mechanism that is dependent on its ADP ribosyltransferase activity. Moreov ExoS deficiency also switched the mode of macrophage death from apoptosis to pro-inflammatory pyroptosis. Altogether, these da demonstrate a dual role for the P. aeruginosa T3SS in the regulation of Caspase-1 mediated IL-1β production and provide new insigh into the mechanisms of immune evasion by this pathogen.